Translocation of nutrient transporters to cell membrane via Golgi bypass in Aspergillus nidulans. - Dimou, Sofia; Martzoukou, Olga; Dionysopoulou, Mariangela; Bouris, Vangelis; Amillis, Sotiris; Diallinas, George (EMBO Rep, 2020)
Nutrient transporters, being polytopic membrane proteins, are believed, but not formally shown, to traffic from their site of synthesis, the ER, to the plasma membrane through Golgi-dependent vesicular trafficking. Here, we develop a novel genetic system to investigate the trafficking of a neosynthesized model transporter, the well-studied UapA purine transporter of Aspergillus nidulans. We show that sorting of neosynthesized UapA to the plasma membrane (PM) bypasses the Golgi and does not necessitate key Rab GTPases, AP adaptors, microtubules or endosomes. UapA PM localization is found to be dependent on functional COPII vesicles, actin polymerization, clathrin heavy chain and the PM t-SNARE SsoA. Actin polymerization proved to primarily affect COPII vesicle formation, whereas the essential role of ClaH seems indirect and less clear. We provide evidence that other evolutionary and functionally distinct transporters of A. nidulans also follow the herein identified Golgi-independent trafficking route of UapA. Importantly, our findings suggest that specific membrane cargoes drive the formation of distinct COPII subpopulations that bypass the Golgi to be sorted non-polarly to the PM, and thus serving house-keeping cell functions.
Keywords: Aspergillus nidulans; Cell Membrane; Fungal Proteins; Golgi Apparatus; Nutrients